The Perceptions of Accountancy Students on the Passing Rate of the Licensure Examination for Certified Public Accountants - Carator, Maria Jean Montibon; Lavilla, Joana Camelle; Pescadero, Christian Paul; Pepania, Artchelene D.; Sumicad Jr., Eligen H. (Faculty Of Islamic Economics and Business, 2024)
Purpose: This study aims to investigates the perceptions of 3rd-year accountancy students concerning the passing rates of the Licensure Examination for Certified Public Accountants (LECPA).Design/methodology/approach: This study utilized a qualitative research design with a multiple case study approach, the researchers employed in-depth interviews, observations, and data mining to explore students’ decisions to persist in pursuing CPA licensure or reconsider their career paths.Research Findings: The results of the study indicated that some participants exhibited strong determination fueled by personal commitment, while others expressed hesitancy due to concerns about exam difficulty and the risk of failure. These insights emphasize the importance of robust support systems for aspiring Certified Public Accountants.Contribution/Originality/Novelty: The findings contribute valuable insights for academic institutions and educators to tailor effective support systems and interventions, advancing the understanding of career choices, educational motivation, and dynamics within the field of accountancy for 3rd-year students. Tujuan Penelitian: Penelitian ini bertujuan untuk mengetahui persepsi mahasiswa akuntansi tahun ke-3 mengenai tingkat kelulusan Ujian Lisensi Akuntan Publik Bersertifikat (LECPA).Desain / metodologi / pendekatan: Penelitian ini memanfaatkan desain penelitian kualitatif dengan pendekatan studi kasus ganda, para peneliti menggunakan wawancara mendalam, observasi, dan penggalian data untuk mengeksplorasi keputusan siswa untuk tetap mengejar lisensi CPA atau mempertimbangkan kembali jalur karir mereka.Temuan Penelitian: Hasil penelitian menunjukkan bahwa beberapa peserta menunjukkan tekad yang kuat yang dipicu oleh komitmen pribadi, sementara yang lain menyatakan keraguan karena kekhawatiran akan kesulitan ujian dan risiko kegagalan. Wawasan ini menekankan pentingnya sistem pendukung yang kuat bagi calon Akuntan Publik Bersertifikat.Kontribusi / Orisinalitas / Kebaruan: Temuan ini memberikan kontribusi wawasan berharga bagi institusi akademis dan pendidik untuk menyesuaikan sistem pendukung dan intervensi yang efektif, memajukan pemahaman tentang pilihan karir, motivasi pendidikan, dan dinamika dalam bidang akuntansi untuk siswa tahun ke-3.